Chemical constituents and cockroach repellent activity of Sudanese Cyperus rotundus rhizomes essential oil - Nour, Azhari H.; Idris, Abeer A.; Ishag, Omer A.; Nour, Abdurahman H.; Alara, Oluwaseun Ruth (Marmara University, 2022)
Cockroaches are among the most adaptive creatures to the environment; they dwell on the earth’s surface for the past millions of years. The presence of cockroaches is posing serious health issues in many countries of the world. Searching for an effective natural repellent agent has become a highly important attempt to control these insects. Hence, this study aimed to evaluate the chemical compositions of essential oil from Sudanese Cyperus rotundus rhizomes and determine their repellent activity against American cockroaches (Periplaneta americana). The obtained essential oil was radish yellow in color, the oil content was 0.73% and forty-four constituents were identified. The most major components were: Isolongifolol (7.63%), longiverbenone (5.61%), β-cadinene (5.54%), and longifolenaldehyde (5.16%). The oil was characterized by sesquiterpenes abundance 52.45% (oxygenated sesquiterpenes 30.72% and sesquiterpenes hydrocarbons 21.73%); whereas, monoterpenes comprised 8.43% (oxygenated monoterpenes 6.81%, and monoterpenes hydrocarbons 1.62%). The experiment showed that the essential oil possesses promising results as a repellent against P. americana. Therefore, conducting more research on isolation, identification of active compounds and extensive tests on other types of cockroaches are priorities in future studies.